Is the Homocysteine Level a Good Predictive Marker for Evaluating Kidney Function in Patients After Percutaneous Nephrolithotomy? - Karlidag, Ismail; Abat, Deniz; Altunkol, Adem; Izol, Volkan; Demir, Erkan; Aridogan, Ibrahim Atilla (Urology Journal, 2018)
Purpose: The purpose of this study is to evaluate the preoperative, early and late postoperative homocysteine levels and its relationship with kidney function in patients after undergoing percutaneous nephrolithotomy (PNL). Materials and Methods: Twenty-three patients with kidney stones underwent PNL and blood samples were taken preoperatively as well as at 48 hours and three months after the operation. The homocysteine level was determined by high pressure liquid chromatography and the fluorometric method in blood samples with ethylenediaminetetraacetic acid. The Cockcroft – Gault formula was used to calculate the glomerular filtration rate (GFR). Non-contrast computed tomography was performed for all patients before surgery. Stone burden was calculated as the sum of the area of each stone in mm2. Results: Fourteen male (60.9%) and nine female (39.1%) patients were recruited for this study, and the median age was 44.3 ± 15.17 (20 – 71) years. There were no statistically significant differences between the preoperative homocysteine level and the level at 48 hours post-operation (P = .460). However, the homocysteine level three months after the operation was significantly lower than the preoperative and 48 hour levels (P = .001 and P = .003, respectively). Conclusion: Renal function, which deteriorated after the PNL procedure, was preserved or improved over time. Homocysteine may be a sensitive indicator to assess the change in renal function pre-and post-PNL.